Comparative Expression Analyses of Pro- versus Anti-Inflammatory Mediators within Synovium of Patients with Joint Trauma, Osteoarthritis, and Rheumatoid Arthritis - Mohammed A. Al-Madol; Mohammed Shaqura; Thilo John; Rudolf Likar; Reham Said Ebied; Michael Schäfer; Shaaban A. Mousa (Hindawi Limited, 2017)
Synovial injury and healing are complex processes including catabolic effects by proinflammatory cytokines and anabolic processes by anti-inflammatory mediators. Here we examined the expression of pro- versus anti-inflammatory mediators in synovium of patients with diagnostic arthroscopy (control), joint trauma (JT), osteoarthritis (OA), and rheumatoid arthritis (RA). Synovial samples from these patients were subjected to RT-PCR and double immunofluorescence confocal microscopy of pro- and anti-inflammatory mediators as well as immune cell markers. Interestingly, pro- and anti-inflammatory mediators were expressed predominantly in granulocytes in patients with JT and in macrophages, lymphocytes, and plasma cells in patients with OA and RA. Interestingly, parallel to the severity of inflammation, proinflammatory mediators IL-1β, TNF-α, and 5-LOX specific mRNA as well as immunoreactive (IR) cells were significantly more abundant in patients with RA and JT than in those with OA. However, anti-inflammatory mediators 15-LOX, FPR2, and IL-10 specific mRNA as well as IR cells were significantly more abundant in patients with OA than in those with JT and RA. These findings show that upregulation of proinflammatory mediators contributes to the predominantly catabolic inflammatory process in JT and RA synovium, whereas upregulation of anabolic anti-inflammatory mediators counteracts inflammation resulting in the inferior inflammatory process in OA synovium.